Meta-synthesis of drivers of the circular business model - Atieh Khodaei; Mahdi Hosseinpour; Mohammad javad Jamshidi; Yoosof Mohamadifar (ارزش آفرینی در مدیریت کسب و کار)
Abstract The present research was conducted through the combination of previous research with the aim of presenting a comprehensive picture of the components and concepts of the drivers of the circular business model. The research methodology is qualitative with a meta-synthesis approach. Accordingly, after searching in reliable domestic and foreign databases, in the time range of 2014 to 2023 for domestic research sand 2010 to 2023 for foreign researches, a number of 97 related studies were evaluated and finally, after multiple screenings, 42 articles were selected. The findings of 42 previous studies related to the research objectives were reviewed, aggregated, combined, and interpreted by means of the seven-step model of Sandelowski and Barroso. Using the coding method, the number of 27 codes, 8 concepts, and 3 components were identified and validated through Cohen's kappa test, and the model of the drivers of circular business model was presented and drawn. The results of this research showed that a wide range of drivers can be used for transition from linear and traditional business models to circular business models and by carefully considering and understanding these drivers, it is possible to strengthen them and finally facilitate the implementation of successful circular business models. Finally, in line with the results of the research, practical suggestions are presented that can provide valuable insight to individuals and business managers and policy makers who seek to improve circular entrepreneurship and increase the entrepreneurial behavior of the society and at operational levels by actors who accompany circular entrepreneurship. Extended Abstract Introduction Our world is currently facing numerous environmental, social and economic challenges, and the consequences of these challenges can be seen in climate change, pollution, loss of biodiversity and resource destruction. Today, researchers have reached a turning point in what the earth can sustain and current living standards are not sustainable in the long term (Toth-Peter et al., 2023). Also, the rapid increase in population puts pressure on the consumption of biological resources, and as a result, governments, businesses and communities are directed to try to preserve the available resources. In contrast to the linear economy, the circular economy approach has attracted a lot of attention, and researchers have highlighted the urgent need to adopt a circular economy and thus conserve resources at all levels (Velenturf & Purnell, 2021). Circular economy is a concept that benefits the environment and mankind (Neves & Marques, 2022). This call has led commercial businesses to transform the existing linear business model into a circular business model (Palmié et al., 2021). In fact, it is very important to change the paradigm from a linear economy to a circular economy to reduce the pressure on the environment and improve the security of the supply of raw materials. Under this new paradigm, which is governed by the requirements of "reduce, reuse and recycle", the extraction of primary resources is minimized by increasing the useful life of existing resources and materials (Neves & Marques, 2022). The circular business model is also defined as an organizational ecosystem to create, absorb and provide value by extending the useful life of products through remanufacturing, repairing or designing long-life products (Bocken et al., 2016). Therefore, the increasing popularity and need of the circular business model at the global level creates the need for a better understanding of the various drivers of the circular business model. Despite examining the benefits and drivers of the circular business model, the implementation of the circular business model in the manufacturing industry and many businesses is still limited (Urbinati et al., 2017). Therefore, much more theoretical and empirical effort is needed to analyze the enabling and driving factors for designing circular business models (Hussain & Malik, 2020); that is, the factors that encourage the transition to a circular business model (De Jesus & Mendonça, 2018). However, previous studies have identified drivers for the change towards circular business models in a fragmented and separate manner, which encourages the implementation of circular business models; which, due to the great importance of circular business models in order to gain sustainable competitive advantage and create multiple values of economic development, social justice and environmental protection, requires a complete investigation, aggregation and interpretation. In fact, the existing articles in this field have addressed some of the indicators and drivers of circular business models separately; therefore, the current research aims to answer the following question by choosing a different perspective from previous researches and identifying, combining and deeply understanding the components, concepts and indicators with a systematic and comprehensive analysis in a meta-composite way: What is the pattern of drivers of the circular business model? Theoretical framework The concept of circular economy has received increasing attention due to the conditions of the global ecosystem, the need to reuse materials and economic justifications (Charef & Emmitt, 2021). This concept is defined as an economic system focused on the reuse of products and materials to conserve natural resources as a starting point where "environmental and social values are vital in every part of the system" (Reike et al., 2018). The main idea of the circular economy is to close material loops and thus avoid waste, reduce pollution and minimize the use of intact resources. This should maximize the useful life of products by recreating processes like those in nature (Sauvé et al., 2016). The concept has also sparked some inevitable deep debates at business and organizational levels globally, as the world claims to transition to a resource-efficient model, particularly in business areas that focus on rotational business models. (Diaz et al., 2021). A circular business model can be defined as “the logic of how to create, deliver and capture value with and within material closed loops” (Antikainen et al., 2018). The adaptation of circular business models enables businesses not only to operate sustainably, but also to create a competitive advantage (Ghisellini et al., 2016). Circular business models are networked in nature and therefore require different actors in the value network to work together towards common goals. There is a need to consider changes in value creation for a wide range of actors, as there are often game changes in business models. Research methodology This research is applicable in terms of purpose. In order to collect data, all the researches published in the field of circular economy in reliable domestic and foreign databases based on the keywords "business model", "circular business" and "circular business model", in relation to "circular economy" is defined for entrepreneurship and management journals. 97 related studies were evaluated and finally, after reviewing, 42 articles were selected. The basis of validity of the present research is theoretical validity. The meta-synthesis approach based on the guidelines of Sandelowski and Barroso was applied in this study. This approach is a systematic review of qualitative research findings to create a new interpretation through a logical and consistent seven-step process. The meta-synthesis process includes defining the research questions and goals, organized reviewing of the literature, searching and choosing related studies, extracting textual information, analyzing and synthesizing qualitative findings, controlling the quality, and, finally, providing the findings. Research findings Cohen's kappa test was used to measure the quality. The results of calculating the kappa statistic in this research show that the kappa coefficient is equal to 0.732, which indicates the reliability of this research. Using the coding method based on the analysis done with the help of content analysis, the content of 42 final articles has been selected and a total of 27 codes, 8 concepts and 3 components have been identified. Based on the findings of the research, the final model of the drivers of the circular business model has been complied according to the following figure.